Analysis of treatment of large abdominal malignancies in children complicated with abdominal compartment syndrome: Report of six cases. Issue 17 (April 2017) - Le-Xiang, Zeng; Yao-Hao, Wu; Na, Li; Rong-Lin, Qiu; Jia-Jia, Zhou; Wen-Li, Jiang; Jie, Zhang; Xiao-Geng, Deng
Abstract : Abstract: To explore effective treatment of large abdominal malignancies in children complicated with abdominal compartment syndrome (ACS). Six children with large abdominal malignancies complicated with ACS were admitted to our department from January 2013 to January 2016, and the changes in their breathing, heart rate, oxygen saturation, abdominal circumference, bladder pressure, and urine output, as well as the treatment measures and outcomes, were retrospectively analyzed. The 6 children included 1 child with bilateral nephroblastoma, 1 child with abdominal alveolar rhabdomyosarcoma, 1 child with right ovarian malignant teratoma complicated with abdominal glioma, 1 child with abdominal malignant teratoma, 1 child with right nephroblastoma, and 1 child with left adrenal gland neuroblastoma. All patients were treated in a timely manner. The first 4 children underwent abdominal cavity decompression through surgical resection of the tumor, and the ACS was successfully cured allowing for follow-up care, whereas the last 2 patients failed to receive emergency surgery and eventually died due to the gradual aggravation of ACS. Decompression through surgical resection of the tumor is the only effective measure for treating large abdominal malignancies in children complicated with ACS.